Molecular screening of feline morbillivirus - Manoraj, Hemadevy (2015)
Feline morbillivirus (FmoPV) is a negative-sense, single stranded RNA virus that belongs to the family Paramyxoviridae. The FmoPV has been recently detected in cats in Hong Kong and Japan, and is associated with tubulointerstitial nephritis. In this study, urine and blood samples were collected from 35 client-owned cats presented to the Universiti Veterinary Hospital- Universiti Putra Malaysia (UVH-UPM) and participating private veterinary clinics. Healthy and renal/urinary-diseased cats were included in this study. Serum urea-creatinine and urine specific gravity analyses were performed to assess the renal or urinary disease status in these cats. FmoPV screening of the collected samples were conducted using two-steps conventional reverse-transcriptase polymerase chain (RT-PCR) assay amplifying a part of N-gene sequence of the virus. Of the 25 cats screened for the blood samples, 1 cat (4.0%) was tested positive for FmoPV. In addition, 17 out of 27 cats (63.0%) screened for urine samples were tested positive for FmoPV. From 17 cats screened for both blood and urine samples, 1 cat (5.9%) was tested positive for FmoPV. The prevalence of FmoPV in Malaysia is 48.6%. Chi square analysis revealed no significant association between renal/urinary diseased cats and FmoPV (P=0.11).